A Computer Solution of The First Order Irreversible Chemical Reaction to Maximize The Overall Yield Product - Youssef, N.A. (Asian Journal of Chemistry, 2010)
This paper shows that for any first order irreversible chemical reaction, we can determine the reaction time (t0 hours) required to maximize the overall yield of product per hour for different values of the down time between the reaction cycles (t0 hours) and the reaction rate constant (k hr–1) at a specified temperature (T). Two iterative processes are applied to obtain the reaction time t0, the modified iterative M.I. and the half-interval search procedure H.I. The first method involves relative little computation-time. The initial values of t0 for different values of tc and k are calculated initially for the M.I. method. Also, the initial values for the isolated interval (a, b) are calculated for the H.I. search procedure. The two methods are represented in computer FORTRAN IV program. The Wang Computer (Model No. PC-S2-2) is used for obtaining the numerical results for the chemical problem. In conclusion, the accuracy of the results is discussed.